Forestry In The Digital Era: Drone Technology And Ai In Forest Conservation - Faizah, Naela Mikyalul (PT. Anagata Sembagi Education, 2025)
In the face of accelerating deforestation and climate change, the integration of digital technologies into forest conservation strategies has become increasingly vital. This study explores the transformative role of drone technology and artificial intelligence (AI) in modern forestry management. By employing high-resolution aerial imagery from drones and leveraging AI-based data analysis, forest monitoring has shifted from reactive to proactive approaches. The research highlights how drones facilitate real-time surveillance, detect illegal logging activities, and assess forest health with greater precision. Meanwhile, AI enhances pattern recognition for biodiversity tracking, fire prediction, and resource allocation. Through case studies in Indonesia and Brazil, this paper demonstrates significant improvements in conservation outcomes where digital tools were applied. The findings suggest that integrating drones and AI not only improves efficiency and accuracy in forest management but also supports evidence-based policymaking for sustainable forestry. The study concludes with recommendations for broader implementation and the need for capacity building among conservation stakeholders.